First-line managers' experience of guideline implementation in orthopaedic nursing and rehabilitation: a qualitative study - Erika FJORDKVIST; Maria HÄLLEBERG NYMAN; Madeleine WINBERG; Eva JOELSSON-ALM; Ann Catrine ELDH (BMC, 2024)
Abstract Background First-line managers have a unique role and potential in encouraging the use of evidence-based clinical practice guidelines (CPGs) and thus serve the provision of safe patient care. In acute and planned hospital care, effective yet safeguarded nursing procedures are a necessity. Little is currently known about how first-line managers engage in supporting the adoption of evidence-based nursing care and about what barriers and enablers there are for implementation of CPGs in the orthopaedic care context. Purpose To investigate first-line managers' experience of clinical practice guideline implementation in orthopaedic care. Methods This qualitative interview study included 30 first-line nursing and rehabilitation managers in 17 orthopaedic units in Sweden. A deductive content analysis, with the Ottawa Model of Implementation Leadership as a guide, was employed. Results To the first-line managers, any guideline implementation required them to balance contexts, including their outer context (signified by the upper-level management and decision-makers) and their inner context, including staff and patients in their unit(s). Acting in response to these contexts, the managers described navigating the organization and its terms and conditions; using relations-, change-, and task-oriented leadership, such as involving the staff; motivating the change by emphasizing the patient benefits; and procuring resources, such as time and training. Even though they knew from past experience what worked when implementing CPGs, the first-line managers often encountered barriers within the contexts that hampered successful implementation. Conclusions Although first-line managers know how to effectively implement CPGs, an organization's terms and conditions can limit their opportunities to fully do so. Organizational awareness of what supports and hinders first-line managers to offer implementation leadership can enhance opportunities to alter behaviours and conditions for the benefit of CPG implementation. Trial registration The study was registered as NCT04700969 with the U.S. National Institutes of Health Clinical Trials Registry on 8 January 2021.